A SEMIOTIC ANALYSIS OF ASIAN WOMEN’S STEREOTYPES ON CHO CHANG - Nugraheni, Priskilla Trisna; Wenas, Michael Bezaleel; Utami, Birmanti Setya (Seni Media Rekam ISI Surakarta, 2023)
Stereotypes against Asians emerge and develop as a form of propaganda for Americans. Cho Chang, a character from the Harry Potter film series, exemplifies negative stereotypes of Asian women. Accordingly, this study aims to identify which stereotypes of Asian women correspond to the existing reality. Using Barthes’ semiotic theory, this study employed qualitative analysis. The findings indicate stereotypes that fit the audience’s interpretation, i.e., Asian women are exotic and charming, Asians are academically intelligent, and Asian women easily change their partners. Meanwhile, stereotypes that do not fit with the audience’s interpretations include: Asians are clumsy, weird, and disliked by Americans, and the “Dragon Lady” image of Asian women who is cunning, sadistic, and untrustworthy.